1979
DOI: 10.1097/00000658-197912000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Esophagus

Abstract: The treatment results of the Rotterdam working group on esophageal cancer during the period January 1970-January 1978 were assessed. A total number of 328 patients were treated: 230 males and 98 females. Of the 133 patients eligible for a combined treatment modality i.e. preoperative radiotherapy and surgery, 52 showed irresectable or metastatic disease during operation. The five year actuarial survival rate of the 81 patients, in whom curative surgical resection of the tumor was performed, amounted to 21%. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this study, we found that age and gender, dose and frequency of radiotherapy and the size of surface under radiotherapy are the important prognostic factors for survival. Several previous studies have also found longer survival times for women (Van Andel, 1979;Kinoshita et al, 1982;Shimada et al, 1999). Thus, the recurrence or progression of oesophagus carcinoma may relate to a hormonal factor such as testosterone or androgen.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we found that age and gender, dose and frequency of radiotherapy and the size of surface under radiotherapy are the important prognostic factors for survival. Several previous studies have also found longer survival times for women (Van Andel, 1979;Kinoshita et al, 1982;Shimada et al, 1999). Thus, the recurrence or progression of oesophagus carcinoma may relate to a hormonal factor such as testosterone or androgen.…”
Section: Discussionmentioning
confidence: 82%
“…In the 81 patients from the earlier period who completed the combined treatment the actuarial corrected 5-year survival was 21 per cent, and a significantly better survival for females than for males was found (42% versus 12%) (3). The difference between the two periods is not explained by the operation mortality, which was similar in both periods.…”
Section: Reduced Sample Methods (N=8)mentioning
confidence: 76%
“…The question is whether combined treatment is better than surgery alone: an improved survival rate of 25% versus 13.5% was reported by Akakura et al over 2 consecutive time periods, whereas other simultaneous studies offeredidentical [9] or even worse [13] results. A better survival experience in Rotterdam [14] could be due to a high proportion of females (one-third) in that series. Concentrated radiation appeared to be better in the series of Kelsen et al, but in a small sample.…”
mentioning
confidence: 81%
“…Distant progression was common [3,15] and more frequent in irradiated patients, contrary to local recurrences which were less frequent [8]. Overall, long-term results of the combined treatment appeared to be better than radiation alone in a priori operable patients [4,14,16].…”
mentioning
confidence: 90%